2005
DOI: 10.1111/j.1460-9568.2005.04515.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct pyrogenic input from prostaglandin EP3 receptor‐expressing preoptic neurons to the dorsomedial hypothalamus

Abstract: Fever is induced by a neuronal mechanism in the brain. Prostaglandin (PG) E2 acts as a pyrogenic mediator in the preoptic area (POA) probably through the EP3 subtype of PGE receptor expressed on GABAergic neurons, and this PGE2 action triggers neuronal pathways for sympathetic thermogenesis in peripheral effector organs including brown adipose tissue (BAT). To explore pyrogenic efferent pathways from the POA, we determined projection targets of EP3 receptor-expressing POA neurons with a special focus on rat hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
229
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(252 citation statements)
references
References 51 publications
18
229
2
3
Order By: Relevance
“…Third, separate GABAergic neurons may represent cold-sensitive and warm-sensitive neurons in the POA (Nakamura and Morrison, 2008), and stimulating both populations simultaneously may offset each other's function.…”
Section: Leprbmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, separate GABAergic neurons may represent cold-sensitive and warm-sensitive neurons in the POA (Nakamura and Morrison, 2008), and stimulating both populations simultaneously may offset each other's function.…”
Section: Leprbmentioning
confidence: 99%
“…This modulates the SNA in BAT, a heat generating tissue that regulates core temperature (Nakamura, 2011). Previous studies have suggested that cold-inhibited and warm-activated GABAergic POA neurons innervate BAT-related DMH/DHA and rostral raphe pallidus (rRPa) neurons (Nakamura et al, 2002(Nakamura et al, , 2005(Nakamura et al, , 2009Yoshida et al, 2009). Indeed, cold exposure potently stimulates while warm/thermoneutral exposure strongly inhibits BAT thermogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al, 1989;Schlesinger, 1993;Piper et al, 1994;Strauss and Strauss, 1994;Lundstrom, 1999). Furthermore, since a large amount of palGFP is produced and distributed not only on the somatodendritic membrane but also on the axonal membrane of infected neurons (Furuta et al, 2001), the vector has been used as a highly sensitive anterograde tracer in the CNS (Nakamura et al, 2002(Nakamura et al, , 2004(Nakamura et al, , 2005Ito et al, 2007). In the present study, we used the recombinant Sindbis virus vector as a tool for single-neuron labeling of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using combined retrograde labeling and immunocytochemistry revealed that EP3 prostanoid receptor-positive GABAergic PO/AH neurons project to the sympathetic premotor neurons in the rostral raphe pallidus (rRPA). The projections are either direct or via the dorsomedial hypothalamus (DMH) [16,17]. Bilateral microinjections of GABA-A receptor agonists or antagonists into the rRPa or DMH, blocked the fever induced by intra-PO/AH PGE2 applications.…”
Section: Thermoregulatory Neuronal Network Comprising Po/ah Thermosementioning
confidence: 99%